Control interno en la oficina de presupuesto y racionalización y su relación con la ejecución presupuestal en las municipalidades distritales de El Dorado, periodo 2015 - Reátegui Terrones Jandy Paola (2016)
This paper entitled "Internal Control in the budget office and rationalization and its relationship with the budget execution in the district municipalities of El Dorado, 2015 period", aims to answer the question: Is there a relationship between the internal control in the budget office and rationalization and budget execution in the district municipalities of El Dorado, 2015 period ?, whose possible answer: Hi: If there is a relationship between the internal control in the budget office and rationalization and budget execution in the district municipalities El Dorado, period 2015. And H0: There is no relationship between the internal control in the budget office and rationalization and budget execution in the district municipalities of El Dorado, 2015 period. This work corresponds to the non-experimental and correlational design; I counted on a population consisting of the number of workers of the budget and streamlining each of the municipalities in the province of El Dorado area. In order to collect relevant for the development of labor information, a survey and analysis was applied obtaining the following recultados: After applying the test of "Pearson" (Because the first variable is cuanlitativa second type and quantity) The program threw Table No. 2, where it is shown that there is a significant relationship to 0.003 (And as stipulated by this test: While the significance level is less than 0.05, there is a positive relationship). Also, the obtained relationship can be seen in Chart No. 7 (by dispersing points), where the results of the variables are presented as reference coordinates used to mark points around the graphic; The relationship is perceived because the points are raised so that it is possible to draw a line between them. Also I came to the following conclusion: I get to determine the existence of a relationship between the internal control in the budget office and rationalization and budget execution within the four municipalities district objects under study in the province of El Dorado